Sinos River Hydrographic Basin: urban occupation, industrialization and environmental memory - Nunes,M. F. (2015)
This article presents an analysis of the process of industrialization and urbanization of the Sinos Valley in Rio Grande do Sul state, Brazil, starting from the establishment of leather goods and footwear manufacturing in the region during the 19th century when tanneries and factories producing footwear and/or components for footwear began to appear, and with special attention to aspects related to the environmental impact on the Sinos river hydrographic basin. The article is based on both bibliographic and documentary research and also draws on biographical narratives of workers with links to the leather goods and footwear industry obtained using ethnographic method. It was found that contemporary environmental conflicts emerge from within a memory of work and an environmental memory in which the factories, the unplanned urbanization, and the utilization of water and other natural resources form a chain of significance. Significance that precludes any form of fragmented analysis that isolates any of these aspects from the others: the economic, socio-historic, cultural, political, or the environmental.